Soliton solutions of nonlinear fractional differential equations with their applications in mathematical physics - Cevikel, A. C.; Aksoy, E. (SOC MEXICANA FISICA, 2021)
In this study, the generalized Kudryashov method has been used to investigate a certain type of nonlinear fractional differential equations. Firstly, we proposed a fractional complex transform to convert fractional differential equations into ordinary differential equations. Three applications were given to demonstrate the effectiveness of the present technique. The results show that this method is very effective and powerful mathematical tool for solving nonlinear fractional equations arising in mathematical physics. As a result, abundant types of exact solutions are obtained.
Keywords: Exact solutions; modified Riemann-Liouville derivative; fractional complex transform; fractional differential equations; 1ST INTEGRAL METHOD; WAVE SOLUTIONS; MODELS; Physics